Walking with Non-Invasive Ventilation Does Not Prevent Exercise-Induced Hypoxaemia in Stable Hypercapnic COPD Patients. (3rd September 2015) - Walker, David Johannes; Walterspacher, Stephan; Ekkernkamp, Emelie; Storre, Jan Hendrik; Windisch, Wolfram; Dreher, Michael
Abstract: Background: Non-invasive positive pressure ventilation (NPPV) in addition to supplemental oxygen improves arterial oxygenation, walking distance and dyspnea when applied during exercise in stable hypercapnic COPD patients. The aim of the current study was to investigate whether NPPV without supplemental oxygen is capable of preventing severe exercise-induced hypoxemia in these patients when applied during walking. Methods and Results: 15 stable hypercapnic COPD patients (FEV1 29.9 ± 15.9%) performed two 6-minute walk tests (6MWT) with a rollator in a randomized cross-over design: using either supplemental oxygen (2.4 ± 0.7 L/min) or NPPV (inspiratory/expiratory positive airway pressure of 28.2 ± 2.8 / 5.5 ± 1.5 mbar) without supplemental oxygen. Results: 10 patients were able to complete both 6MWT. 6MWT with supplemental oxygen resulted in no changes for PO2 (pre: 67.3 ± 11.2 mmHg vs. post: 65.6 ± 12.0 mmHg, p = 0.72) whereas PCO2 increased (pre: 50.9 ± 8.1 mmHg vs. post: 54.3 ± 10.0 mmHg (p < 0.03). During 6MWT with NPPV PO2 significantly decreased from 66.8 ± 7.2 mmHg to 55.5 ± 10.6 mmHg (p < 0.02) whereas no changes occurred in PCO2 (pre: 50.6 ± 7.5 mmHg vs. post: 53.0 ± 7.1 mmHg; p = 0.17). Walking distance tended to be lower in 6MWT with NPPV compared to 6MWT with supplemental oxygen alone (318 ± 160 m vs. 377 ± 108 m; p = 0.08). Conclusion: The use of NPPV during walking without the application of supplemental oxygen does not prevent exercise-induced hypoxemia in patients with stable hypercapnic COPD.